Factors playing a role in the development of emotional labor behavior of clinical nurses. Issue 3 (20th February 2020) - Baksi, Altun; Arda Sürücü, Hamdiye
Abstract: Purpose: This study aimed to investigate spirituality, sociodemographic features, and occupational features as predictors of nurses' emotional labor. Design and Methods: The study is descriptive cross‐sectional and correlational research. Findings: The results demonstrated that there was a statistically significant positive relationship between the nurses' spirituality and the subdimension of intimate behavior ( r = .545) ( P < .05). Regarding the nurses' in‐depth behaviors, the study found that spirituality ( β = .550) and the number of patients that the nurses were responsible for ( β = −.154) were statistically significant predictors ( P < .05). The subdimensions of superficial behavior, spirituality ( β = .498), and rechoosing the profession ( β = −.142) were statistically significant predictors as well ( P < .05). Practice Implications: For the development of emotional labor in clinical nurses, administrators should be sensitive to nurses' spiritual values.